ARTS DOMINANCE IN CALENDAR GRAPHICS DESIGN - Apele, Diāna; Treiliņa, Ina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Art, in a way, is a form of communication, which allows the artist to express their view to the world, show their interpretation and let others see the world through the eyes of the artist. Calendars are the most popular and long-term means of advertising, which is why their design requires a lot of attention. It is important that it does not only look good, but also provides information, fulfils the function of a promotional souvenir and creates an image throughout the entire year ahead. Graphic design is a form of visual communication whose purpose is to solve visual and graphic problems using artistic approaches provided by typography, different printing technologies, or image processing techniques, mechanical or analogue methods, or digital, with the aim to create a graphic design work or solve a graphic problem. Graphic design is more like a visual intermediary between the message and its recipient and a way of delivering the message to the recipient. The Aim of the Article: study graphics as the dominant feature of art in the design of calendars created by modern Latvian artists and analyse expert interviews to find out the opinions of specialists in the field about the significance of the content and design of artistic calendars nowadays. The research results were obtained using theoretical research methods: the study, analysis and evaluation of scientific and journalistic literature and Internet sources, which reveals the essence of the problem in question; expert interviews were carried out as well, which are empirical research methods.